Evidence of Co-learning through a Relational Pedagogy: Indigenizing the Curriculum through MIKM 2701 - Root, Emily; Augustine, Stephen; Snow, Kathy; Doucette, Mary (The Canadian Journal for the Scholarship of Teaching and Learning, 2019)
In the winter term of 2016, Cape Breton University launched a revised version of a second year Mi’kmaw Studies course entitled Learning from the Knowledge Keepers of Mi’kmaki (MIKM 2701). This course was designed to be led by local Elders and Knowledge Keepers with facilitation support from university faculty. It was designed by course facilitators as a dual-mode course, with the opportunity for students to participate face-to-face and online, and the excitement it generated quickly went “viral.” In this paper, we describe the experiences of the participants in the course through an analysis of their own reflections on the 13 weeks of instruction. The aim of this analysis is to share course design considerations for post-secondary institutions attempting to “Indigenize the academy” at a course level, but also to evaluate the process of co-learning as it was evidenced in the course as a means to address educational complexity and decolonization efforts in the classroom. Au cours du trimestre d’hiver de 2016, l’Université du Cap-Breton a lancé une version révisée d’un cours de deuxième année d’études mi’kmaw intitulé « Learning from the Knowledge Keepers of Mi’kmaki » (Apprendre avec les gardiens du savoir du Mi’kmaki) (MIKM 2701). Ce cours avait été conçu de façon à être dirigé par des aînés et des gardiens du savoir originaires de la région avec le soutien de professeurs de l’université. Il avait été conçu par les facilitateurs du cours en tant que cours bi-mode, qui donnait l’occasion aux étudiants de participer face à face et en ligne, et l’enthousiasme qu’il a généré s’est rapidement propagé. Dans cet article, nous décrivons les expériences des participants inscrits dans le cours par le biais d’une analyse de leurs propres réflexions sur les 13 semaines d’enseignement. L’objectif de cette analyse est de partager les considérations concernant la conception du cours à l’intention des établissements d’enseignement post-secondaire qui voudraient « indigéniser l’université » au niveau d’un cours, mais également ...